„Vitae archiepiscoporum Gnesnensium” Klemensa Janickiego – geneza i wczesna recepcja - Milewska-Waźbińska, Barbara (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
The article concerns a series of biographical epigrams entitled Vitae archiepiscoporum Gnesnensium written by Klemens Janicki at the request of Archbishop Andrzej Krzycki. The author considers historical and iconographic context of this cycle.